Relationship Between the Application of a Full Day School System and Stress Levels in Junior High School - Maulidiyah Junnatul Azizah Heru; Atika Jatimi; Fakhrun Nisa Fiddaroini; Achmad Syamsudin (Jurnal Ners, 2019)
Introduction: This research presents the relationship between the schools which implemented full day school and which did not apply the full day school to the level of stress students in junior high schools. This was influenced by the existence of regional autonomy as part of government policy and orientation toward quality education institutions.Methods: This research used a quantitative correlational approach to obtain the significance of the relationship between the variables examined.  The sampling technique used  purposive sampling, with samples of 37 students for a group of cases and 37 students to control groups. Data analysis was conducted using the Kolmogorov Smirnov test.Results: The results showed that in the case group there were 83.78 experiencing mild stress and 16.22 experiencing moderate stress, while in the control group there were 89.19 experiencing mild stress, and 10.81 experiencing moderate stress with P- value 0.000 (<0.05).Conclusion: The conclusion of this study is that more moderate stress levels are found in students who apply the Full Day School System in Junior High School.